Diagnosis of acute myelomonocytic leukemia in a patient with extramedullary testicular lesion - N. K. Guskova; O. N. Selyutina; I. B. Lysenko; E. A. Guskova; A. K. Donskaya; N. Yu. Samaneva; E. A. Kapuza; T. F. Pushkareva (Онкогематология, 2022)
A complex clinical case of acute myelomonocytic leukemia with extramedullary lesion of the testis is presented. patient yu., born in 1968, applied to the National Medical Research Centre for Oncology (Rostov-on-don) after an injury to the inguinal region. ultrasound was performed: in the right testicle in the middle third, a mass of 30 × 23 × 16 mm was revealed. A biopsy was performed: the morphological picture is characteristic of a typical seminoma. Orchofuniculectomy was performed on the right. Histopathological conclusion: the morphological picture is more characteristic of a typical seminoma, but does not allow excluding lymphoma. In order to differentiate between a germ cell tumor and a lymphoproliferative disease, an immunohistochemical study of the tumor tissue, a morphological and immunophenotypic study of the bone marrow were performed. According to the immunohistochemical data, the morphological picture and immunophenotype of tumor cells are characteristic of extranodal NK/T-cell lymphoma of the testis with Cd4 co-expression. However, according to the myelogram data, 20 % of morphologically heterogeneous blast cells were found: with round or bean-shaped nuclei, delicate mesh structure of chromatin, 1–2 nucleoli and a monocytoid form of nuclei with indistinct nucleoli. The cytoplasm of varying basophilia degrees, vacuolized, with delicate azurophilic granularity. The content of the monocytoid population was increased (19 %), represented mainly by promonocytes, which corresponds to acute myelomonocytic leukemia. According to flow cytometry, the immunophenotype of blast cells corresponds to acute myeloid leukemia with Cd56 co-expression. In connection with the new data obtained, the histological preparation was revised again with the expansion of the immunohistochemical study. Result: morphological picture and immunophenotype of tumor cells are characteristic of acute myelomonocytic leukemia with extramedullary lesions of the right testicular tissue. final diagnosis: acute myelomonocytic leukemia with extramedullary lesion of the right testicle, with Cd56 co-expression. The presented clinical case showed the need to use a wide range of diagnostic techniques to determine the nature of the disease. The results of morphological and cytometric studies of the bone marrow were decisive in establishing the diagnosis of M4 acute myeloid leukemia with extramedullary lesions of the right testicle in this patient.